Síntese e caracterização de nanocompósitos poliuretano/dióxido de titânio - Silva, Vinícius Demétrio da (2012)
Due to the demand of the current market of polymeric materials and materials based on a polymeric structure, as some composites and nanocomposites, the development of new materials is fundamental. Thus, this work aims to study the synthesis and experimental characterization of nanocomposites polyurethane/titanium dioxide, using commercial raw materials. The nanocomposites were synthesized by in situ polymerization reactions in which an inorganic filler was added, titanium dioxide (TiO2), in the following proportions by weight in relation to the mass obtained from the pure polymer: 0.5%, 1.0%, 2.0%, 3.0%, 5.0%, 7.0% e 10.0%. These reactions were based in poli(-caprolactone) (PCL) and 1,6-diisocyanate hexane (HDI). The materials were characterized by Infrared Spectroscopy Fourier Transform (FTIR), Scanning Electron Microscopy (SEM), Differential Scanning Calorimetry Analysis (DSC), Thermo-gravimetric analysis (TGA) and Thermodynamic and Mechanical Analysis (TDMA). Analyzing the results obtained, the materials that showed better thermo-mechanical performance were the polymers with 2.0, 3.0 and 5.0% of TiO2. Although showing a lower degradation temperature when compared to the materials with 7.0 and 10.0% of TiO2, the additions of 2.0, 3.0 and 5.0% proved to be the most efficient in tensile tests. It can be concluded that the nanocomposites synthesized by in situ polymerization showed, in general, superior thermal properties (degradation temperature) and mechanical properties when compared to the pure polymer. It is noteworthy that there was no need of any kind of treatment in the commercial filler, which leads to a reduction in the cost of the process